Fenton processes for AOX removal from a kraft pulp bleaching industrial wastewater: optimisation of operating conditions and cost assessment - Ribeiro, João Peres (2022)
AOX emissions to water are a key environmental aspect in the pulp and paper industry being limited by EU Ecolabel criteria. In this work, response surface methodology was used to optimise Fenton and photo-Fenton processes for AOX removal from a kraft pulp mill bleaching wastewater. Focus on the specific stream where AOX is higher reduces the wastewater volume to treat and the associated costs. Moreover, there is a need to assess the effect of treatment in parameters other than AOX, such as BOD5, COD and colour content, which were also quantified in this work. Operational costs were determined for both processes, including chemical consumption and energy input (in the case of photo-Fenton process). The photo-Fenton process exhibited better performance than the classic Fenton process, achieving 90 % AOX removal against 80 % for the Fenton process, higher colour content removal and enhanced wastewater’s biodegradability (BOD5/COD ratio). Moreover, photo-Fenton process showed lower operational costs for maximum AOX removal: 46.5 € m−3 wastewater treated or 0.45 € g−1 AOX removed, against 70.0 € m−3 wastewater treated or 0.78 € g−1 AOX removed by the Fenton process.